A plant peptide hormone phytosulfokine promotes somatic embryogenesis by maintaining redox homeostasis in Cunninghamia lanceolata - Hao, Z.; Wu, H.; Zheng, R.; Li, R.; Zhu, Z.; Chen, Y.; Chen, J
Somatic embryogenesis (SE)are widely used for studying the mechanisms of embryo development. However, little is known about the underlying mechanisms especially in woody plants. Previous studies have revealed a SE system has been well-established for Cunninghamia lanceolata, but in a genotype-dependent manner which limits its application in practice. Here, we found that phytosulfokine (PSK), a plant peptide hormone, can not only increase SE efficiency, but also establish SE in those recalcitrant genotypes of C. lanceolata. PEM browning and determination of hydrogen peroxide (H2 O2 ) content by dichlorofluorescein (DCF)staining indicated that a reactive oxygen species (ROS)burst occurred rapidly after PEMs were transferred to the SE induction medium. Transcriptome analysis and qRT-PCR validation showed that PSK treatment helped to maintain ROS homeostasis by decreasing the activity of PRXs in the early SE induction. This appropriate redox microenvironment medicated by PSK treatment might be helpful for expression induction of SE related genes like WOX2 in the early SE induction. Further analyses suggested that PSK promotes C. lanceolata SE induction partially through the decreasing of H2 O2 levels which is necessary but not sufficient for SE induction in recalcitrant genotypes of C. lanceolata. Furthermore, heterologous overexpression of ClPSK in Arabidopsis led to an enhanced SE induction and resistance to H2 O2 stress. Taken together, our study identifies a biological function for the plant peptide hormone PSK, extends our knowledge about SE in woody trees and provides a valuable tool for establishing an efficient and genotype-independent SE system in C. lanceolata and other coniferous trees.